Can Osteoarthritis be Cured by Mesenchymal stem cells (MSCs)? A Literature Review - Mohamed Hussein (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
Osteoarthritis (OA) is a degenerative joint disease that affects millions of people worldwide. The disease frequently results in discomfort, edema, and stiffness, which can impair movement, make everyday tasks challenging, and even render a person disabled. Since osteoarthritis is presently incurable, researchers are working hard to find new treatments. Adult Mesenchymal stem cells (MSCs) are the most common stem cells used in the therapy of OA in clinical trials. They are simple to extract for researchers from bone marrow or adipose. Depending on the kind of tissue that contains them, MSCs can develop into cartilage, bone, muscle, tendon, ligaments, or fat. For this reason, scientists are researching MSCs in OA stem cell therapies. According to research, MSCs produce substances that promote healing and reduce pain. According to some research, they may aid in reducing pain, swelling, and loss of motion when injected into a joint. Researchers conduct an examination of articles that are in accordance with the issue to be studied. Articles used in literature review are obtained through the database of international journal providers through PubMed, we investigated clinical studies and discussed what happened in these clinical studies and the extent of the effectiveness of stem cells in treatment of osteoarthritis. Different patients have responded differently to this therapy. While some people have experienced pain others have not. Research is still required to determine whether stem cell therapies for OA are effective and why some people respond to the therapy more favorably than others.